Mitigation of non-linear four-wave mixing phenomenon in a fully optical communication system - Petr Ivaniga; Tomáš Ivaniga (Universitas Ahmad Dahlan, 2020)
This paper aims to point out the nonlinear phenomenon occurring in coarse/dense wavelength division multiplex (C/D-WDM) systems. This phenomenon has to betaken into account during the design of the optical network itself, as wavelengthsin the optical fiber are constantly densified. The paper points out the emergence of the non-linear four-wave mixing (FWM) phenomenonand how it relates to the dispersion in the optical fiber together with the transmit power. The output of the paper is a proposed design of the system that points to the improvement of the bit error rate (BER) with a suitable choice of dispersion and suitable transmission power.